1990
DOI: 10.1111/j.1945-5100.1990.tb00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and thermal histories of chondrules in the Chainpur (LL3.4) chondrite

Abstract: Transmission-electron-microscopy (TEM) and optical data suggest that chondrules in the Chainpur (LL3.4) chondrite experienced varied thermal and deformation histories prior to the final agglomeration ofthe meteorite. Chainpur may be regarded as an agglomerate or breccia that experienced little deformation or heating during and after the final accumulation and compaction of its constituents.One chondrule in Chainpur was impact-shocked to high pressures (-20-50 GPa), almost certainly prior to final agglomeration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This suggests that the chondrules experienced different conditions and amounts of alteration on the parent body. This, in turn, suggests a mixing of chondrules from sources across the parent body, which is consistent with the suggestion of Ruzicka (1990) (based on the variation in shock levels between chondrules) that Chainpur is an agglomerate composed of chondrules with widely diverse histories before compaction. It is notable that, of our samples, only CR2 exhibits a mixing line requiring phases with different 129 Xe*/I ratios, which is suggestive of a contribution of iodine and planetary xenon from more than one event.…”
Section: How To Explain the Wide Variation Of Chainpur Chondrule Ages?supporting
confidence: 76%
See 1 more Smart Citation
“…This suggests that the chondrules experienced different conditions and amounts of alteration on the parent body. This, in turn, suggests a mixing of chondrules from sources across the parent body, which is consistent with the suggestion of Ruzicka (1990) (based on the variation in shock levels between chondrules) that Chainpur is an agglomerate composed of chondrules with widely diverse histories before compaction. It is notable that, of our samples, only CR2 exhibits a mixing line requiring phases with different 129 Xe*/I ratios, which is suggestive of a contribution of iodine and planetary xenon from more than one event.…”
Section: How To Explain the Wide Variation Of Chainpur Chondrule Ages?supporting
confidence: 76%
“…Although Ruzicka (1990) found at least one chondrule had suffered significant shock deformation, there is no requirement that any of the chondrules studied here should have experienced comparable levels of shock, given that Chainpur appears to be an agglomerate. In addition, shock is predominantly a process that is magnified at grain boundaries (Stöffler et al, 1988;Stöffler et al, 1991).…”
Section: How To Explain the Wide Variation Of Chainpur Chondrule Ages?mentioning
confidence: 93%
“…The first one is the protoenstatite inversion to produce a range of ortho-clino-enstatite intergrowths, as observed in type 3 chondrites (TopelSchadt and Miiller, 1985;Ruzicka, 1990); the second one, primarily based on the evidence illustrated in Fig. 5, is the clinoenstatite inversion in the ortho-enstatite stability field during subsequent thermal metamorphism.…”
Section: Origin Of High-resolution Transmission Electron Microscopic mentioning
confidence: 90%
“…In turn, experiments for time periods up to 24 d at 800 up to 1045 "C performed by Brearley and Jones (1993) on clinoenstatite-richer grains revealed no or very minor inversion. Previous HRTEM investigations of unshocked or slightly shocked H3 to H6 chondrites and L3 and LL3 chondrites have shown that enstatite is mainly twinned clinoenstatite in unmetarnorphosed type 3 chondrites (Tieschtitz, Mezo-Madaras, and Chainpur), with rare orthoenstatite crystals (Ashworth, 1981;Topel-Schadt and Miiller, 1985;Ruzicka, 1990). In turn, the abundance of orthoenstatite increases with petrographic type, as in the Quenggouk, Allegan, and Butsura H4-6 series (Ashworth, 1980(Ashworth, , 1981.…”
Section: Origin Of High-resolution Transmission Electron Microscopic mentioning
confidence: 92%
See 1 more Smart Citation